2022
DOI: 10.1039/d1ee04022g
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting metal-inward diffusion-induced degradation through strong chemical coordination toward stable and efficient inverted perovskite solar cells

Abstract: The inward diffusion of metal electrode is one of the main reasons which deteriorates the long-term device stability of perovskite solar cells (PSCs). Here, we adopt a simple additive engineering...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 54 publications
0
37
0
Order By: Relevance
“…Similarly, Yang and coworkers introduced the modification of 1,3,5-triazine-2,4,6-trithiol trisodium salt (TTTS) to BCP. 158 As shown in Fig. 8b, they reported that there were three sulfide ions with strong lone pairs of electrons in TTTS, which could form strong chemical coordination with metal electrodes to prevent metal diffusion.…”
Section: Alternative Electrodesmentioning
confidence: 93%
“…Similarly, Yang and coworkers introduced the modification of 1,3,5-triazine-2,4,6-trithiol trisodium salt (TTTS) to BCP. 158 As shown in Fig. 8b, they reported that there were three sulfide ions with strong lone pairs of electrons in TTTS, which could form strong chemical coordination with metal electrodes to prevent metal diffusion.…”
Section: Alternative Electrodesmentioning
confidence: 93%
“…[ 153 ] Yang et al observed the device with modified BCP by 1,3,5‐triazine‐2,4,6‐trithiol trisodium salt (TTTS) showed stronger stability because of blocked Au diffusion. [ 154 ] Similarly, 2D graphene oxide (rGO) was proved an effective barrier to block Au diffusion, which was introduced between CuSCN and Au achieving stability of T 95 of 1000 h under MPP, 60 °C. [ 110 ] Park et al used atomic layer deposition (ALD)‐grown Al‐doped ZnO as a barrier between PCBM and Ag, in which this film layer not only can collect electrons effectively, prevent the evaporation of perovskite degradation products but also prevent the reaction between electrode and the active layer.…”
Section: Stability Test Protocols Of Pscs Under Combined Elevated Tem...mentioning
confidence: 99%
“…Many efforts have been carried out to apply novel interlayers to prevent metal and halogen ion interdiffusion. [ 25,26 ] Wang et al. introduced polyethyleneimine into the ammoniated PH1000 as an effective barrier for the electrochemical reaction between the perovskite precursor solution and the Ag grid electrode, as a result, the device had a significant enhancement in PCE from 4.67% to 14.52%, and maintained 20% of initial PCE under continuous illumination for 300 h. [ 19 ] Jeong et al.…”
Section: Introductionmentioning
confidence: 99%
“…Many efforts have been carried out to apply novel interlayers to prevent metal and halogen ion interdiffusion. [25,26] Wang et al introduced polyethyleneimine into the ammoniated PH1000 as an effective barrier for the electrochemical reaction between the perovskite precursor solution and the Ag grid electrode, as a result, the device had a significant enhancement in PCE from 4.67% to 14.52%, and maintained 20% of initial PCE under continuous illumination for 300 h. [19] Jeong et al applied graphene as a protection interlayer in PSCs, leading to a significant improvement in PCE, as well as enhanced thermal stability which retained 75% of initial PCE after heating at 100 °C for 180 min. [27] Ham et al used diethanolamine additive in SnO 2 electron transport layer to inhibit the migration of iodide ions.…”
mentioning
confidence: 99%